MANAJEMEN PENGELOLAAN SAMPAH OLEH DINAS LINGKUNGAN HIDUP KABUPATEN BATANG - Hikmah Insani, Nurul; Larasati Setianingsih, Endang; Lituhayu, Dyah (Journal of Public Policy and Management Review, 2024)
Batang Regency had significant challenges related to waste management. The amount of waste in Batang Regency was quite large, but its management was still not optimal, as evidenced by the spike in daily waste tonnage from 150-200 tons in 2018-2019 to 500 tons in 2023. This research aimed to analyze waste management by the Environmental Service (DLH) of Batang Regency. The research method used was descriptive with a qualitative approach, with data sourced from interviews with informants and documentation, as well as data analysis using triangulation. The research results showed that although regulations such as Law No. 18 of 2008 and Regent's Regulation No. 40 of 2019 existed, their implementation was not yet optimal in dealing with the increase in daily waste volume. DLH faced significant challenges in managing B3 waste, which was generally handled by the private sector, as well as expanding efforts to increase public awareness through outreach and collaboration with waste banks. The DLH organizational structure, including the Regional Technical Implementation Unit (UPTD), showed quite good performance, but still required improvement in human resource qualifications and training to optimize waste management in Batang Regency.